Trail Blazers : An Illustrated Guide to the Women Who Explored the World - Lisa Graves (London Xist Publishing, 2014)
By land, sea, and air, women have traveled the globe, blazing a trail of exploration, discovery and empowerment. This illustrated guide of explorers tells the incredible stories of the women who went against all odds to see the world and go beyond the limits set by their times. The second title in Lisa Graves' Women in History series, Trail Blazers is an indisputable resource for today's children.
Keywords: Where We Are in Place and Time -- -Exploration